External training load monitoring in young gymnasts in competitive period - Freitas, Elisângela Gamarano de; Carrara, Paulo; Debien, Paula Barreiros; Silva, Cristiano Diniz; Bara Filho, Maurício (Brazilian journal of physical education and sport, 2023)
The aims of this study were to characterize the distribution of external training load metrics in women's artistic gymnastics; and check for correlation between metrics and competitive results. Seven gymnasts, aged 11.3±0.4 years, participated in the study. Three micro cycles before the Brazilian Championship in the 10-12 years old category and two micro cycles after the championship were monitored. The external training load was accessed daily and represented by the number of elements performed in training sessions in five dimensions (four devices and total). Friedman test between the external training load metrics and the micro cycles, and linear regressions between the external training load metrics and the classification in the competition were performed. The weekly amount of elements varied according to the apparatus, with significant reductions in the team from the pre to post-championship phase (p=0.04). The regressions showed trivial to moderate correlation (R2=0.01 to R2=0.43) between the number of elements and the competitive results. In this sense, coaches must: be aware to the continuous control of training loads; reflect on whether they guarantee the individualization of external training loads; and balance the ideal amounts of repetitions with actual results in competition, in order to provide career longevity for young gymnasts.